S90 The nature and duration of symptoms and time to starting treatment comparing older with younger pulmonary tuberculosis patients. (15th November 2016) - Abbara, A; Hardman, E; Collin, SM; Kon, OM; Mahomed, Z; Sullivan, JAL; Buell, K; Hansel, T; Corrah, T; Davidson, RN
Abstract : Introduction and objectives: In 2013, Public Health England (PHE) reported that 39% of pulmonary tuberculosis (TB) patients >65 years old started treatment >4 months after symptom onset compared to 25% of patients aged 15–44 years. A longer symptomatic period, particular if smear positive, may result in increased transmission and poorer treatment outcomes. We investigated age-related differences in symptom duration and time to starting TB treatment in a large UK cohort of TB patients. Methods: The cohort comprised patients on the London TB register (LTBR) who were treated at Northwick Park Hospital between 2002–2015. Patients aged >65 years were compared with a random sample of patients aged 18–40 years, with respect to symptoms, symptom duration at presenting to secondary care and time to starting treatment after presenting to secondary care. Results: 357 patients over 65 and 517 younger patients were identified. Demographics for the total number of patients are included in Table 1 . Data were available for 489 of the younger group and 73 of the older group. 26 of the >65s (35.6%) and 9 (1.8%) of the 65s were diabetic. Conclusions: This study has identified that a potential cause for a delay in diagnosis in the elderly may be related to the decreased frequency of 'classical' TB symptoms in those >65 years of age. Clinicians need to be vigilant despite the lack of these symptoms. Median duration of symptoms was twice that in older patients versus younger patients (90 days versus 45) with a longer time to starting treatment (7 days versus 2). The total duration (in months) from symptom onset was also higher at 3 months versus 2 months. A higher proportion of older patients (32%) started treatment greater than 4 months from symptom onset compared to 13.1% in younger patients. Biases in this work including recording bias due to the retrospective nature of symptom recording, the effect of selecting younger patients from more recent years (to improve data availability) and the low proportion of patients over 65 which had symptom and treatment data available.